A novel method for the determination of trace sulfonylurea herbicides by introducing a hybrid stationary phase to common capillary - Jing-Hua Yang; Xiao-Mao Zhou; Yu-Ping Zhang; Jun Chen; Hai-Weng Ma (Adsorption Science & Technology, 2017)
In this paper, a novel polymerized fiber doped with metal–organic frameworks (UIO-66(Zr)-NH 2 ) was developed in a capillary by microwave irradiation. The fiber was successfully prepared using 4-vinyl pyridine as the monomer and ethylene glycol dimethacrylate as the cross-linker to reinforce its durability. The resultant fiber was applied to extract sulfonylurea herbicides from environmental soil and water samples before analysis with high-performance liquid chromatography. The optimization of different parameters affecting solid-phase microextraction procedure was carried out. Under the optimum experimental conditions, the extraction capability of the hybrid fiber was two times greater than that of the polymer fiber without UIO-66(Zr)-NH 2 .The proposed hybrid fiber extraction method exhibited low detection limits (0.19–1.79 µg/l), good precision (<12.0%), and wide linear range (10–700 µg/l). Satisfactory recoveries of sulfonylurea herbicides were obtained with spiked soil and water samples in the range of 75.7–94.2 and 82.2–95.3%, respectively.